Sosialisasi 3 Dosa Besar Dalam Pendidikan Untuk Menanamkan Nilai Karakter Pada Siswa Sekolah Dasar - Nur Farida; Alfatamara Risqa; Aulida Yuni Rachmawati; Linatul Af'idah; Khanif Hidayah; Fitria Sa'adatun Ni'mah; Kamila Fithrachatun Nisa; Zaidatum Muhaniyyah; Fadlli Haris Muafa; Ardiyan Habli Manaf; Bayu Irawan; Irvan Avianto; Taufiqurrohman Taufiqurrohman; Subhi Tri Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explores the role of socialization methods in overcoming three major sins in school education: Bullying, Sexual Violence, and Intolerance. This research examines the effectiveness of the character values socialization program in overcoming major sins in education. The research results show that this method has a positive impact on students' understanding and application of values such as integrity, responsibility and cooperation. This also forms a solid foundation of character. The success of this program cannot be separated from collaboration between schools and families, where the involvement of parents and teachers is very important. Research shows that socialization methods can improve the quality of elementary school education, create an academic environment and foster strong student character.